High genetic diversity and demographic stability in Aechmea kertesziae (Bromeliaceae), a species of sandy coastal plains (restinga habitat) in southern Brazil. (1st March 2018) - Goetze, Márcia; Capra, Fernanda; Büttow, Miriam Valli; Zanella, Camila Martini; Bered, Fernanda
Abstract: Forest-dwelling taxa of the Brazilian Atlantic rainforest experienced range contractions during the glacial periods of the Quaternary. In contrast, species of drier environments, such as the restinga, may show different patterns. Here, we investigated a bromeliad from the southern Brazilian restinga, Aechmea kertesziae . We used nine nuclear microsatellite markers, two non-coding plastid sequences and controlled pollination experiments to examine the genetic structure and diversity across the geographical distribution of the species. Our results suggest demographic stability for A. kertesziae during the Quaternary, despite other restinga species showing demographic expansion. Aechmea kertesziae shows high genetic diversity, which is probably the result of its self-incompatibility, allied to the long-term persistence of the populations, constant population sizes and clonal reproduction. A strong phylogeographical break was identified with the plastid markers, recovering two main evolutionary lineages showing little gene flow between them. However, no geographical barrier could be associated with this deep Pliocene divergence. Moderate levels of genetic structure were detected with nuclear microsatellites, which was associated with a more recent habitat fragmentation process. Conservation efforts should prioritize the establishment of effective gene flow among populations.